Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 11 - Section 11.3 - Integrated Review - Summary on Solving Quadratic Equations: 27

Answer

$x_{1}=\dfrac{-3 + \sqrt{17}}{4}$ and $x_{2} = \dfrac{-3 - \sqrt{17}}{4}$

Work Step by Step

Given $2x^2+3x=1 \longrightarrow 2x^2+3x-1=0$ $a= 2, \ b=3, \ c=-1$ Using the quadratic formula: $\dfrac{-b \pm \sqrt{b^2-4ac}}{2a}$ we have: $\dfrac{-3 \pm \sqrt{3^2-4 \times 2\times (-1)}}{2 \times 2} = \dfrac{-3 \pm \sqrt{9+8}}{4} = \dfrac{-3 \pm \sqrt{17}}{4}$ Therefore the solutions are $x_{1}=\dfrac{-3 + \sqrt{17}}{4}$ and $x_{2} = \dfrac{-3 - \sqrt{17}}{4}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.